Perlindungan Hukum dari Negara Terhadap Masyarakat Fakir Miskin Menurut Konsep Welfare State (Studi Pengentasan Kemiskinan Masyarakat di Kota Palembang) - Muhammad Zainul Arifin; Muhammad Syahri Ramadhan; Happy Warsito; Ardian Nugraha (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2020)
The process of implementing the concept of a welfare state by the Indonesian government towards its people is a problem of poverty. The number of needy people in Indonesia is enormous. This is what underlies poverty to be considered a serious problem so that the Indonesian government provides specific regulations related to poverty handling through the issuance of Law no. 13 of 2001 concerning Management of the Poor. In the South Sumatra region, particularly the city of Palembang itself, the problem of poverty is a big task that must be faced by regional officials and other related agencies. The Social Service of South Sumatra Province stated that Palembang City was the city with the highest number of poor people compared to other districts / cities in South Sumatra. This of course requires the right policies in handling it, one of which is through the issuance of the Regional Regulation of South Sumatra Province Number 7 of 2017 concerning poverty reduction in South Sumatra